The Dose Rate Calculator (DRc) for Luminescence and ESR Dating-a Java Application for Dose Rate and Age Determination. - Tsakalos, E.; Christodoulakis, J.; Charalambous, L. (Archaeometry, 2016)
The Dose Rate calculator (DRc) is a software program written in Java that facilitates the calculation of dose rates and age determinations of materials, for use in palaeodosimetric dating methods. The program runs in a user-friendly interface and provides a number of user-controllable features. Dose rates are calculated using updated conversion and attenuation factors. This paper presents the basic principles that the software takes into account in its calculations.